Molecular plant breeding and genome editing tools for crop improvement - Deka, Pradip Chandra, 1947- (Advances in environmental engineering and green technologies (AEEGT) book series., 2021)
"This book examines the applic ation of various molecular breeding techniques for crop improvements, identification of cultivars, and germplasm preservation"--